2013
DOI: 10.4236/jdm.2013.34026
|View full text |Cite
|
Sign up to set email alerts
|

Serum C reactive protein level in type 2 diabetes mellitus patients attending diabetic clinic in Benin City, Nigeria

Abstract: C reactive protein is sensitive physiological biomarkers of sub clinical inflammation associated with hyperglycemia. The aim of this study is to determine the fasting serum C reactive protein level in type 2 diabetes mellitus patients attending diabetic clinic in Benin City, Nigeria. The population sample consists of 142 subjects. 71 patients were known type 2 diabetes mellitus, while the other 71 were age matched control subjects. Fasting glucose and C reactive protein were estimated using glucose oxidase met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…The level of CRP was significantly higher in female patients when compared to males ( Table 5). Similar to other studies an elevation of serum C-reactive protein was demonstrated in both Males and Females type 2 Diabetes mellitus 27 . CRP was not a significant predictor of the development of the metabolic syndrome in men.…”
Section: Fig 2: Gender Distributionsupporting
confidence: 76%
“…The level of CRP was significantly higher in female patients when compared to males ( Table 5). Similar to other studies an elevation of serum C-reactive protein was demonstrated in both Males and Females type 2 Diabetes mellitus 27 . CRP was not a significant predictor of the development of the metabolic syndrome in men.…”
Section: Fig 2: Gender Distributionsupporting
confidence: 76%
“…They consist of 40 known type 2 diabetes mellitus and 40 aged matched apparently healthy control subjects on routine checkup. They were confirmed to be diabetics and non diabetics respectively using the glucose oxidase method as previously described by Ehiaghe et al (2013).…”
Section: Materials and Methods Subjectsmentioning
confidence: 99%
“…Glucose oxidase method was used in the determination of blood glucose as previously described by Ehiaghe et al (2013). In brief, 10 µl of the standard or test samples was added to 1000 µl of glucose reagent 1, mixed and incubated for 25 minutes at 20 0 C.The absorbance of the standard and test samples was measured against the reagent blank within 60 minutes at a wavelength of 540 nm using a spectrophotometer.…”
Section: Determination Of Blood Glucose Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…C-reactive protein is an inflammatory marker originally found in sera of those that reacted with cpolysaccharide within cellular wall of Streptococcus pnuemonia produced and released by the liver under the stimulation of pro inflammatory cytokines such as interleukin 1 and 6, tumor necrosis factor [9,10]. Alpha 1 -antitrypsin is a protease inhibitor which protects tissue from enzyme inflammatory cells especially neutrophil elastase, but the concentration rises many fold upon acute inflammation, pregnancy, oral contraceptive [11].…”
Section: Introductionmentioning
confidence: 99%